Peixes bentófagos de riachos : dieta dos predadores e disponibilidade das presas. - Silva, Renata Guglielmetti da (2016)
This study investigated the diet of seven species of fish that consume predominantly benthic macroinvertebrates, and the availability of these organisms in the environment. It was tested the hypothesis that while all consume benthic prey, they use these resources differently. Fish and macroinvertebrate were sampled in four streams wich belong to the Pirapó River sub-basin (upper Paraná River Basin). Fish diet was evaluated by the volumetric method. Individual and interspecific variation in diet composition were synthesized by an ordination analysis (PCoA), and interspecific differences in diet composition were tested by a PERMANOVA. To estimate the trophic niche breadth it was used the standardized index of Levins. The abundance of macroinvertebrates was expressed as number of individuals /m². To verify the existence of correlation between the abundance of macroinvertebrates consumed and available in the environment, a Spearman correlation was used. The seven species analyzed essentially consumed aquatic insects, but for most of them were registered significant differences in diet composition. The values for trophic niche breadth were low for all species (<0.35). In general, Chironomidae, Ephemeroptera, Trichoptera and Ostracoda were the most abundant macroinvertebrates in streams. For five of the seven species analyzed, there was no significant correlation between the abundance of macroinvertebrates in the environment and diet. The results showed that although all species feed on the bottom, they utilize the available food resources in the environment differently. The lack of correlation between the abundance of prey consumed and available in the environment for the majority of species suggests that the most consumed preys was not the most abundant in the environment. These results are probably influenced by morphological characteristics and particular food strategies of each predator and also for the morphology and habits of prey.